CONTRACTBOX: Realizing accountable data sharing on the edge using a small scale blockchain - Almstedt, Lennart; Bleeke, Kai; Mahhouk, Mohammad; Jehl, Leander; Kapitza, Rüdiger; Wolf, Lars (Computer Networks, 2023)
The utilization of IoT devices is becoming omnipresent in industrial settings. However, adoption in more rural areas still poses challenges. Especially when processing data on the edge, privacy, data integrity, accountability and data ownership pose challenges since the devices may be easily accessed and manipulated. We present CONTRACTBOX, a system that provides accountable and trusted data sharing based on a publisher–subscriber system, as well as trusted computing on the edge. CONTRACTBOX uses a Trusted Execution Environment to guarantee the confidentiality and integrity of clients’ data and code. Furthermore, it provides security by using WebAssembly to execute the smart contracts in their own sandboxed environment. This design protects the host as well as co-located smart contracts from misbehaving executions. Lastly, it ensures the immutability and accountability of the published data by storing it in a blockchain. We show that CONTRACTBOX can process several thousand publications per second with various payloads and host multiple smart contract runtimes on a single edge device. CONTRACTBOX also achieves up to 35 times higher throughput than a comparable deployment of Hyperledger Fabric.
CRIS-Team Scopus Importer:2023-05-05
Keywords: Blockchain; Smart contract; Trusted Execution; WebAssembly